ANALISIS KEPUTUSAN PEMBELIAN KAOS MERK WELLTRAF DI CIANJUR - Muhammad Rizki; Zeffanya Raphael Wijaya (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to analyze the decision to purchase Welltraf t-shirts in Cianjur. The research approach uses a qualitative-descriptive approach. Informants or respondents amounted to 32 people. Research data obtained through the collection of questionnaires. The results showed that all dimensions of purchasing decisions, namely product choice, brand choice, dealer choice, time and number of purchases, and payment methods received very high responses from the respondents. Welltraf t-shirt sellers must pay attention to all these dimensions, maintain the uniqueness and quality of the product, as well as the best service from the salesperson.